PROTECTION RIGHTS OF CHILDREN IN TERM OF FAMILY RELATIONSHIP FROM ISLAMIC LAW AND MALAYSIAN LAWS: A COMPARATIVE ANALYSIS (International Seminar on Syariah and Law (INSLA), 2020)
Under Islamic law, all human including a child also entitles to haqq (right)and can benefit from it as long as not over the limits prohibited by Allah. This study deals with the protection of the rights of children in terms of a family relationship from Islamic law and Malaysian law. Further, the research will elaborate on the issue of whether the rights of children in Malaysian law are in line with Islamic law or not. The research is library research where the issue will be examined from the perspective of the Quran and the Sunnah as the primary sources of Islamic law and follows with the examination of the statute of Malaysian law as well as the decided cases in Malaysia. In addition, the reference also will be made to opinions to compare the rights of children in Islamic and Malaysian law. There are several rights of children relating with family relationships namely the right to lineage, right to suckling, right to maintenance, right of gender equality among siblings, and guardianship rights. It is found that all these rights seem scattered and did not combine in one statute. Infact, there are a lot more rights of children that have not been identifying and highlight in Malaysian law.